Instrumen Penilaian Disfungsi Seksual Pasien Kanker - Murtiasih, Sri; Gayatri, Dewi; Allenidekania, Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify sexual dysfunction assessment instruments used in population-based studies of cancer patients. The method in this review used a systematic review that began in September - December 2023. Using Ebsco, Scopus, Proquest, and Pubmed databases, the results showed that instruments used to assess sexual dysfunction must have valid and reliable psychometric properties. Conclusion: the choice of sexual dysfunction assessment instrument depends on the type of study and the purpose of the study. Keywords: Cancer Patients, Questionnaire, Reliable, Sexual Dysfunction, Valid